1993
DOI: 10.2307/1591697
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Pancreatitis and Gizzard Erosion Associated with Adenovirus Infection in Chickens

Abstract: Cases of focal necrotic pancreatitis and gizzard erosion in chickens are reported. Intranuclear inclusion bodies were seen in necrotic pancreatic acinar cells and necrotic epithelial cells of the gizzard, and electron microscopy demonstrated virus particles in affected gizzard epithelium. Adenovirus antigens were detected immunohistochemically in these intranuclear inclusion bodies. These findings suggest that the necrotizing pancreatitis and gizzard erosion were associated with adenovirus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
30
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 9 publications
3
30
1
1
Order By: Relevance
“…However, so far, gizzard erosions have been mostly found in slaughtered broiler chickens, and there have been few reports of gizzard erosions in layer chickens. 25 The broiler chickens with gizzard erosion attributable to experimentally induced infection manifested clinical signs of depression and anorexia, 16 and mortality of commercial broiler chicks with gizzard erosion has been reported. 2 In this study, as well as in a previous study by the authors, 15 however, SPF White Leghorn chickens inoculated with 99ZH did not develop clinical signs of disease despite the fact that they harbored gizzard erosions.…”
Section: Discussionmentioning
confidence: 99%
“…However, so far, gizzard erosions have been mostly found in slaughtered broiler chickens, and there have been few reports of gizzard erosions in layer chickens. 25 The broiler chickens with gizzard erosion attributable to experimentally induced infection manifested clinical signs of depression and anorexia, 16 and mortality of commercial broiler chicks with gizzard erosion has been reported. 2 In this study, as well as in a previous study by the authors, 15 however, SPF White Leghorn chickens inoculated with 99ZH did not develop clinical signs of disease despite the fact that they harbored gizzard erosions.…”
Section: Discussionmentioning
confidence: 99%
“…Gizzard erosion associated with FAV in layer chickens, broiler chickens, and quails has been reported [2,5,13,17]. It has been reported that many outbreaks of gizzard erosion associated with FAV occurred frequently in Japanese slaughterhouses and most of FAV isolated from eroded gizzard were of serotype 1 [14].…”
Section: Discussionmentioning
confidence: 99%
“…In the field, gizzard erosion associated with serotype 8 FAV has also been reported. Tanimura et al [17] reported a field cace of gizzard erosion in which intranuclear inclusion bodies were seen in necrotic epithelial cells of the gizzard, and seroptype 8 FAV was isolated from liver samples. In this case, because chicken anemia virus (CAV) was isolated as well as serotype 8 FAV, it was deduced that CAV might have contributed to the outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the gizzard erosions and ulcers in chickens were observed in Japan. FAV serotypes 1 and 8 were isolated from the affected gizzards [2,15,17]. Gizzard erosion was experimentally reproduced in chickens inoculated with isolated FAV serotype 1 [10][11][12][13][14]18].…”
mentioning
confidence: 99%